An Uncommon Complication of Sinusitis in a Young Adolescent. Issue 7 (July 2015) - Shemesh, Amos J.; Panebianco, Nova L.; Chen, Aaron E.
Abstract : Abstract: A young adolescent patient presented to the emergency department with forehead and eyelid swelling after a week of nasal discharge that was suspicious for Pott's puffy tumor. Point-of-care ultrasound facilitated rapid diagnosis and initiation of treatment for a concerning and rare complication of sinusitis, confirmed by computed tomography scan.